Microbiology of vaginal discharge in Nairobi, Kenya. Issue 3 (June 1983) - Mirza, N B; Nsanze, H; D'Costa, L J; Piot, P
Abstract : Among women attending a sexually transmitted disease (STD) clinic in Nairobi with vaginal discharge, Neisseria gonorrhoeae and Chlamydia trachomatis were isolated from the cervix in 32 (26%) of 122 and four (7%) of 58 women respectively. Infection with Trichomonas vaginalis, Candida albicans, Gardnerella vaginalis, and Mycoplasma spp were diagnosed in 42 of 122 (34%), 26 of 110 (24%), 75 of 100 (75%), and 42 of 89 (47%) women respectively. Mixed infections with at least two pathogens were found in 23 (26%) of 89 women examined for all microorganisms. Infection with N gonorrhoeae was significantly associated with abdominal pain.